Draft Annual Plan (1982-83) (Ladakh District) Volume XIII Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1981)
The chief aim of the department of agriculture in the district is to enhance the production of corsair fields especially drying of apricots vegetables and fodder The objectives can be achieved by adopting otter wise and intensive measures or cultivation, No extension of area under cultivation is possible without adequate Irrigation facilities for which various irrigation projects are already under execution, in Till these projects are commissioned our main emphasis lies on the intensive measure of cultivation which include distribution of improved seeds, use of chemical fertilizers plant protection measures and other improved agronomic practices, improved types of seeds of cereals, fodders, vegetable and vegetable seedlings are being distributed by the department every year. Field demonstrations are conducted educated farmers regarding the used of chemical fertilizers, plan protection measures and improved -agronomic practices. Be sides, seed villages of improved varieties of cereals ar6 also laid ’which besides educating the farmers also produce certified seed for further distribution In the field of horticulture budded fruit plants especially drying type of apricot are distributed amongst farmers every year. To improve the quality of the existing inferior types of apricot trees a massive Programme of top working and then budding with improved varietals has been taken in hand already about 9000 such trees have been converted, To save the crop from various post and diseases necessary plant protection measures are taken by the department. In this connection huge qualities of chemicals are distributed at subsidized rates and spraying of fruit plants is done free of cost.
Government of Jammu and Kashmir
Government of Jammu and Kashmir Planning & Development Department
Keywords: District Ladakh at a Glance; Medical Institutions; Middle & Central Schools; Agriculture Proper; Agriculture Farms and Nurseries; Plant protection; Land Reform; Minor Irrigation; Ladakh region of Jammu & Kashmir State; Sheep and Animal Husbandry; Direction and Administration; Training of Technical Research; Forest Building.